FROM DIGITAL SHOPPING EXPERIENCE TO SOCIAL INFLUENCE: EXAMINING THE ROLES OF ONLINE SHOPPING EXPERIENCE AND INFLUENCER MARKETING IN SHAPING CONSUMER TRUST AND LOYALTY IN E-COMMERCE - Purwati, Astri Ayu; Anisa, Nurul; Ugli, Tilovmurodov Dostonbek Furqat; Sarbaini, Sarbaini (Lembaga Riset dan Inovasi Almatani, 2025)
The aim of this research is to analyze the influence of online shopping experiences and influencer marketing on consumer trust and loyalty when shopping via e-commerce platforms (study in the Pekanbaru community). The population in this study is unknown to the people of Pekanbaru. The sampling technique used was the Roscoe method. The sample size for this study was 170 respondents from the Pek-anbaru community. The sampling technique was carried out using non-probability sampling with Purposive Sampling Technique. The data analysis technique uses the Structural Equation Model (SEM) approach with Partial Least Squares (PLS). The results of this research show that online shopping experience and influencer marketing have a significant positive effect on consumer trust and loyalty in the Pekanbaru community, being the most dominant variables in influencing consumer loyalty.